An All Fiber Intrinsic Fabry-Perot Interferometer Based on an Air-Microcavity - Ruth I. Mata-Chávez; Juan C. Hernández-García; Juan M. Sierra-Hernández; Everardo Vargas-Rodríguez; Roberto Rojas-Laguna; Julián M. Estudillo-Ayala; Daniel Jáuregui-Vázquez (Sensors, 2013)
In this work an Intrinsic Fabry-Perot Interferometer (IFPI) based on an air-microcavity is presented. Here the air microcavity, with silica walls, is formed at a segment of a hollow core photonic crystal fiber (HCPCF), which is fusion spliced with a single mode fiber (SMF). Moreover, the spectral response of the IFPI is experimentally characterized and some results are provided. Finally, the viability to use the IFPI to implement a simple, compact size, and low cost refractive index sensor is briefly analyzed.